The relationships between physical fitness attributes and match demands in rugby union referees officiating the 2019 Rugby World Cup - Blair, M. R.; Scanlan, A. T.; Lastella, M.; Ramsey, C.; Elsworthy, N. (International Journal of Performance Analysis in Sport, 2022)
This study examined the relationships between physical fitness attributes and match demands in lead rugby union referees. Eleven referees underwent anthropometric and fitness assessments (40-m sprint, Yo-Yo Intermittent Recovery Test, 1.2-km shuttle run) prior to the 2019 Rugby World Cup. Match activities were assessed via global positioning system devices (total distance, high-speed running distance [>5 m·s-1], average speed, and peak intensities over 1-min, 5-min, and 10-min epochs) and heart rate variables were measured using chest-worn monitors (HRmean, summated-heart-rate-zones, time above 90% HRmax). Forty-metre sprint time was significantly related to maximum speed (P = 0.004; r = -0.79) and high-speed running distance (P = 0.037, r = -0.63) during matches. Likewise, ?7 skinfold thickness was significantly correlated with high-speed running distance (P = 0.01, r = -0.72). Yo-Yo Intermittent Recovery Test, 1.2-km Shuttle Run Test, age, and body mass index exhibited non-significant correlations (P > 0.05, r = -0.58 to 0.53) with match demand variables. Results suggest it may be pertinent for referees to optimise sprint capacity and body fat composition to execute greater high-speed running volumes and reach higher peak speeds during matches. Yo-Yo Intermittent Recovery Test and 1.2-km shuttle run tests are not correlated to specific match activity variables and thus may not be relevant for monitoring of rugby union referees.